As You Sow, So Shall You Reap?: Evaluating Whether Targeted Capacity Building Improves Nonprofit Financial Growth. Issue 3 (11th November 2016) - Faulk, Lewis; Stewart, Mandi J.
Abstract : Foundations' capacity‐building grant programs strive to bolster performance and outcomes for their nonprofit grantees. Yet with few outcome evaluations of such programs, we have limited understanding of whether these capacity‐building efforts achieve their intended result. This study evaluates fifteen years of data for one foundation's capacity‐building grant program to understand whether targeted capacity building for financial management and development contributes to nonprofit financial growth. The authors examine the management–performance link in this context and inform sector leaders who dedicate resources to capacity‐building programs about the outcomes of these efforts.